The Mediating Role of Talent Development in the Relationship between Talent Attraction and Talent Retention in Research and Development Centers: A Field Study at the Solar Devices Development Unit (UDES) in Bou Ismaïl. - TCHANTCHANE, Imede (Journal of Excellence for Economics and Management Research, 2026)
The study aimed to examine the mediating role of talent development between talent attraction and talent retention in research and development centers, using the descriptive approach, targeting a sample of researchers at the Solar Devices Development Unit (UDES), estimated at (30). The study relied on a questionnaire for data collection, and the analysis was conducted using the SmartPLS program.The study concluded that there is a moderate level of talent attraction, and high levels of talent development and talent retention. It also found that talent attraction and talent development together have predictive and adequate capability for talent retention. Talent attraction is an important factor in enhancing talent retention and is positively associated with talent development. In addition, talent development has a strong effect on talent retention and represents a complementary partial mediation between talent attraction and talent retention. The study recommends, in the context of talent management, that it should be made a priority in managing research competencies, and that it is an integrated process primarily based on talent development